A tribo Lavoisiereae (Melastomataceae) no Planalto Diamantina, Minas Gerais, Brasil - Moreira, Kassio Vinicio Chaves (2022)
Lavoisiereae is one of the richest tribes of Melastomataceae with expressive diversity in the campos rupestres of Bahia, Goiás and Minas Gerais states. The Diamantina Plateau is located between Grão Mogol and Serra do Cipó in the Espinhaço Range Minas Gerais portion with a high number of species and rate of endemism in the family. We present the taxonomic treatment of Lavoisiereae in the Diamantina Plateau, providing an identification key for the species, morphological descriptions, taxonomic comments, flowering, fruit, and geographic distribution data. The current inventory cataloged 67 species, of which 65 belong to Microlicia and two to Rhynchanthera; and, up to now, 19 species are considered endemic to the region.